Aquinas, Aristotle, and the Promise of the Common Good - Keys, Mary M (Cambridge University Press, 2013)
This book, or whatever is good in it, is truly a common good. I am delighted to thank some of the many teachers, colleagues, family members, and friends without whose help this book never would have come to be, or would have come to be quite differently. Because I am, alas, a quintessentially absent-minded professor, I first want to apologize to and to thank anyone I have accidentally omitted here.